Confining Concrete Columns with FRP Materials - Sultan Erdemli Gunaslan; Abdulhalim Karasin (European Scientific Journal, ESJ, 2017)
Fiber Reinforced Polymers (FRP) as a kind of composite materials have became widespread in the strengthening of reinforced concrete structures as an alternative way of traditional strengthening methods. Usage of such polymers as an important application of composites for strengthening has rapidly increased in recent years. Confinement of concrete as a type of inelastic, non-homogenous, non-linear and brittle material has considerable advantages in strengthening with externally bonded by FRP. The lightweight and high strength capacity of FRP sheets and strips which may eliminate the low tension capacity and brittle behavior of concrete sections gain considerable increase in construction industry. In this study codes for strengthening concrete columns investigated to discuss the confinement effect of concrete by FRP material including the mechanical properties.